The effect of rebozo technique on fetal head descent in singleton cephalic pregnancies at 36–40 weeks of gestation - Kusila Devia Rahayu; Setyowati Setyowati; Ermiati Ermiati; Ira Kartika; Taufik Hamzah (Universitas Airlangga, 2026)
Introduction: Descent of the fetal head into the birth canal is a crucial sign of readiness for normal delivery. In a singleton pregnancy with cephalic presentation, failure of the fetal head to descend into the birth canal by 36-40 weeks of gestation can make normal delivery difficult. In the third trimester of singleton pregnancies with cephalic presentation, the Rebozo technique can be used as a non-pharmacological nursing intervention to facilitate the descent of the fetal head into the birth canal. Objective: The purpose of this study was to evaluate the effectiveness of the Rebozo technique influences the fetus's head entering the birth canal during 36-40 weeks of gestation. Methods: This study utilized a quasi-experimental pre and post-test design involving 44 participants, evenly split into intervention and control groups, focused on pregnant women in a community health center in Bandung Regency, West Java Province, Indonesia. Non-probability purposive sampling was used; the inclusion criteria consisted of pregnant women aged 36-40 weeks, with cephalic presentation, height over 145 cm, and healthy pregnancies. The Rebozo technique, which includes the shifting and shaking the apple techniques, was applied to the intervention group twice a week over two weeks. This was conducted by maternity nurses and health workers during prenatal care classes at a community health service center in West Java, Indonesia. Head descent was assessed via abdominal palpation using the fifth palpation method, with data analyzed through the Mann-Whitney U test. Results: The analysis revealed a statistically significant increase in fetal head descent after employing the Rebozo technique (P-value=.001, P-value<.05). These results indicate a significant difference between the control and intervention groups (Z = -5.425; P-value=.001). Thus, the Mann-Whitney U test demonstrates that the Rebozo technique affects the descent of the fetal head in pregnant women at 36 to 40 weeks of gestation. Conclusion: Maternity nursing interventions using the Rebozo technique help accelerate the descent of the fetal head into the birth canal during singleton pregnancies with cephalic presentation. Health workers can apply this technique in the third trimester to prepare for a normal delivery. Keywords: birth canal; fetal position; head descent; normal delivery; nursing intervention